Sleep and Circadian Rhythm Association with Sperm Head Defects in Infertile Males - Mona Sharma; Anmol Garg (Journal of Infertility and Reproductive Biology, 2025)
Male factor infertility can be due to defects in the semen quality and sperm parameters. The sperm head contains the acrosomal enzymes and the DNA required for fertilization. Defects in the sperm head morphology can be a major factor associated with male infertility. Lifestyle changes alter sleep and circadian rhythm which has shown to affect the quality of semen. Circadian rhythm is the normal cycle of physical, emotional, and behavioural changes the body undergoes every 24 hours. Circadian rhythm has an impact on sleep quality and spermatogenesis, thus disrupted circadian rhythm can alter sperm production. Sperm acrosome contain many proteins responsible for fertilization, acrosin being commonest of the proteases. Acrosin activity is essential for fertilization thus changes in the acrosin activity can affect fertilization outcome. This review will highlight the association of sleep and circadian rhythm with sperm acrosin activity and head defects.